Particle Fluxes at the Australian Southern Ocean Time Series (SOTS) Achieve Organic Carbon Sequestration at Rates Close to the Global Median, Are Dominated by Biogenic Carbonates, and Show No Temporal Trends Over 20-Years - Wynn-Edwards, Cathryn A.; Shadwick, Elizabeth H.; Davies, Diana M.; Bray, Stephen G.; Jansen, Peter; Trinh, Rebecca; Trull, Thomas W. (Frontiers in Earth Science, 2020)
Particle fluxes at the Southern Ocean time series (SOTS) site in the Subantarctic zone (SAZ) south of Australia (~47°S, 142°E, 4600m water depth) were collected from 1997 – 2017 using moored sediment traps at nominal depths of 1000m, 2000m and 3800m. Annually integrated mass fluxes showed moderate variability of 14 ± 6 g m-2 yr-1 at 1000m, 20 ± 6 g m-2 yr-1 at 2000m and 21 ± 4 g m-2 yr-1 at 3800m. Particulate organic carbon (POC) fluxes were similar to the global median, indicating that the Subantarctic Southern Ocean exports considerable amounts of carbon to the deep sea despite its high-nutrient, low chlorophyll characteristics. The interannual flux variations were larger than those of net primary productivity as estimated from satellite observations. Particle compositions were dominated by carbonate minerals (> 60% at all depths), opal (~10% at all depths), and particulate organic matter (~17% at 1000m, decreasing to ~10% at 3800m), with seasonal and interannual variability much smaller than for their flux magnitudes. The carbonate counter-pump effect reduced carbon sequestration by ~8±2%. The average seasonal cycle at 1000m had a two-peak structure, with a larger early spring peak (October/November) and a smaller late summer (January/February) peak. At the two deeper traps, these peaks became less distinct with a greater proportion of the fluxes arriving in autumn. Singular value decomposition (SVD) shows that this temperate seasonal structure accounts for ~80% of the total variance (SVD Mode 1), but also that its influence varies significantly relative to Modes 2 and 3 which describe changes in seasonal timings. This occurrence of significant interannual variability in seasonality yet relatively constant annual fluxes, is likely to be useful in selecting appropriate models for the simulation of environmental-ecological coupling and its role in controlling the biological carbon pump. No temporal trends were detected in the mass or component fluxes, or in the time series of the SVD Modes. The SOTS observations provide an important baseline for future changes expected to result from warming, stratification, and acidification in this globally significant region.